Analisis Kesulitan dan Tantangan Mahasiswa PGSD Unismuh dalam Mengajar di SD Bontomanai Makassar - Akbar, Siti Sarah Aulia; Ashar; Sri Rahayu; Fajria Salsabila (Jurnal Riset Evaluasi Pendidikan, 2024)
PGSD Unismuh Makassar during the implementation of Advanced PLP in teaching at SDI Bontomanai. Using a survey method with a questionnaire as a data collection technique, this study involved 4 respondents to assess changes in feelings, experiences, and difficulties and challenges during Advanced PLP activities. The results showed the difficulties and challenges faced by students that before participating in the Advanced PLP, students experienced feelings of anxiety and worry related to greater teaching responsibilities, classroom management, increasing student learning motivation, adapting to the use of innovative learning media and information technology, adjusting learning materials and limited learning facilities and difficulty finding appropriate teaching materials.